1995
DOI: 10.1073/pnas.92.13.5915
|View full text |Cite
|
Sign up to set email alerts
|

Coiled bodies contain U7 small nuclear RNA and associate with specific DNA sequences in interphase human cells.

Abstract: Coiled bodies (CBs) are nuclear organelles whose structures appear to be highly conserved in evolution.In rapidly cycling cells, they are typically located in the nucleoplasm but are often found in contact with the nucleolus. The CBs in human cells contain a unique protein, called p80-coilin. Studies on amphibian oocyte nuclei have revealed a protein within the "sphere" organelle that shares significant structural similarity to p80-coilin. Eukaryotic cells can be viewed as if they were a mixture of compartment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
274
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(289 citation statements)
references
References 23 publications
14
274
0
1
Order By: Relevance
“…U7 snRNPs are strongly associated with CBs (Frey and Matera 1995;Pillai et al 2001), and although U1 snRNPs do not accumulate prominently in CBs at steady state, they likely transit through them (Sleeman and Lamond 1999).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…U7 snRNPs are strongly associated with CBs (Frey and Matera 1995;Pillai et al 2001), and although U1 snRNPs do not accumulate prominently in CBs at steady state, they likely transit through them (Sleeman and Lamond 1999).…”
Section: Discussionmentioning
confidence: 97%
“…Assembly of the U7 snRNP is mediated by a specialized SMN complex that also lacks Sm D1 and D2, but contains Lsm10 and Lsm11 instead (Pillai et al 2003). Otherwise, assembly and nuclear import of U7 snRNPs resembles the pathway for spliceosomal snRNPs (Stefanovic et al 1995), and U7 snRNPs are predominantly localized to CBs with low levels being present in the nucleoplasm (Frey and Matera 1995;Pillai et al 2001). Thus, both the spliceosomal U snRNPs and the U7 snRNP, along with many, but not all, of the snRNP-specific proteins are highly enriched within CBs.…”
Section: Introductionmentioning
confidence: 99%
“…It will be instructive to investigate whether coiled bodies move through interchromosomal channels, or along an underlying nuclear matrix, and whether specific motor proteins are required. Alternatively, as some coiled bodies have been found associated with specific chromosomal loci, including gene clusters that encode U snRNAs and histone mRNAs (Frey and Matera, 1995;Smith et al, 1995), and as there is direct evidence that chromosome movements take place in several cell types (Li et al, 1998; review by Zink and Cremer, 1998), it is possible that the movements of coiled bodies are related to underlying movements of chromosome loci to which they are attached. On the other hand, as Frey et al (1999) showed that the frequency of colocalization of coiled bodies with artificial U1 and U2 snRNA genes depends on the transcriptional activity of the gene array, the movement of a coiled body might be the result of the termination of transcription and the subsequent release of the coiled body from a particular chromosome locus.…”
Section: Discussionmentioning
confidence: 99%
“…In the cell, much of the U7 snRNP is found in Cajal (coiled) bodies, "spheres" in Xenopus oocytes (Wu & Gall, 1993;Wu et al+, 1996), and these nuclear organelles are located near the histone genes in oocytes (Callan et al+, 1991) and in mammalian cells (Frey & Matera, 1995;Matera, 1999), suggesting a role for the coiled bodies in histone pre-mRNA processing+ Some of the xSLBP1 in the frog oocyte is also located in the spheres (Abbott et al+, 1999)+ One possibility is that xSLBP1 may function in a distinct subnuclear compartment+ The histone genes have remained tightly clustered throughout evolution, suggesting that there is selective pressure keeping them closely linked (Wang et al+, 1996a(Wang et al+, , 1996b)+ One reason for this tight clustering may be that the genes are localized in a region of the nucleus specific for histone mRNA processing+ Ninety-five percent of the U7 snRNA in the Xenopus oocyte nucleus is present in spheres (Wu & Gall, 1993)+ Spheres are found dispersed in the nucleoplasm and some are physically attached to the chromosomes at histone gene loci in amphibian oocyte lampbrush chromosome spreads (Callan et al+, 1991)+ Recently Gall and coworkers have shown that xSLBP1 is present in the spheres of the amphibian germinal vesicle (Abbott et al+, 1999)+ A region of xSLBP1, including part of the RBD and the C-terminal region, is capable of directing the xSLBP1 to coiled bodies (Abbott et al+, 1999)+ The spheres also contain RNA polymerase II and coilin (Bellini & Gall, 1998), which has also been shown to associate with the U7 snRNP (Bellini & Gall, 1998)+ Localization of xSLBP1 to the spheres (coiled bodies) may be important for efficient histone pre-mRNA processing in vivo+ The 1-2-1 protein may be deficient in localizing to the coiled bodies or may not interact with unknown factor(s) necessary for processing in vivo, but not in vitro+ In nuclear extracts, any nuclear substructures are disrupted allowing interaction of factors that may be physically separated in the nucleus in vivo+ It is also likely that histone premRNA processing is coupled to histone gene transcription in vivo, as is polyadenylation (McCracken et al+, 1997)+ Thus in vivo there may be a defined pathway by which the histone pre-mRNA processing machinery is assembled and this pathway could be disrupted in nuclear extracts+ Differences in metabolism of the same RNA molecule transcribed from a gene and injected into the nucleoplasm are likely to be observed in many cases+ Differences in the "masking" of mRNAs have been observed in Xenopus oocytes depending on whether synthetic pre-mRNA was injected or whether the premRNA was expressed from an injected gene (Meric et al+, 1996;Matsumoto et al+, 1998)+ It is likely that many steps in nuclea...…”
Section: The Xslbp1 Rna Binding Domain Has Multiple Functionsmentioning
confidence: 99%